A RESEARCH IN THE HEALTH SECTOR ON THE EFFECT OF ORGANIZATIONAL CLIMATE AND PERCEIVED ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Third Sector Social Economic Review, 2021)
Organizational citizenship behavior, which expresses the behaviors that employees display voluntarily and for the benefit of the organization, beyond the role requirements, is the main concept focused in the study. The aim of the study is to determine the relationship between perceived organizational support, organizational climate and organizational citizenship behavior. In the research, data were collected from 200 employees in one public and one private hospital in Menteşe district of Muğla province by using the survey technique. According to the analysis results, it was been determined that there is a significant and positive relationship between organizational climate and organizational citizenship behavior and its sub-dimensions, altruism and civic virtue. Therewithal, it was determined that there is no significant relationship between perceived organizational support and organizational citizenship behavior, but it has been faund that there is a significant and positive relationship between conscientiousness and civic virtue sub-dimensions of organizational citizenship behavior.
Keywords: Organizational Citizenship Behavior; Organizational Climate; Perceived Organizational Support